Repositioning North Atlantic Treaty Organization (NATO): The New Security Dilemma on Trans–Atlantic Relations Amid Shifting Global Geopolitics - George, Daniel C.; Alverdian, Indra (Journal of Strategic and Global Studies, 2025)
The shifting global geopolitics have led to a new security dilemma in Europe, especially in trans–Atlantic relations. NATO as the vanguard of the trans–Atlantic defense pact is faced with transitional conditions of non-conventional threats that return to conventional threats. Due to the shift in the new global order, these threats require a repositioning for NATO to counter the new security dilemma amidst shifting global geopolitics. By referring to the three asserted pillars–the return of conventional warfare on the European continent; a more assertive Russia in the European continent under Vladimir Putin; and the geopolitical of China's rise impacted trans–-Atlantic relations, as factors of the new securities dilemma in the context of trans-Atlantic relations, this research aims to analyze the impact of the new security dilemma amidst shifting global geopolitics toward the repositioning of NATO and its consequences on the trans–Atlantic relations using the integration of Mackinder’s Heartland Theory with Jervis’ Security Dilemma.